Risk Analysis and Reducing Measures in the Tunneling Project of Tabriz Metro Line 2 - Mohammad Darbor; Hamid Chakeri; Mehdi Tabarmaye; Hamed Baghali; Alireza Talebinejad (Analytical and Numerical Methods in Mining Engineering)
Risk management and control are essential tools in various engineering fields, particularly in tunneling projects, which are inherently associated with a high degree of uncertainty and risk. Due to these uncertainties, risk management plays a crucial role in such projects. Given the complexity of tunneling, especially in urban environments, it is vital to identify, evaluate, and analyze risks throughout the project lifecycle. This study examines the geotechnical conditions of Tabriz Metro Line 2, taking into account factors such as the tunnel boring machine (TBM), support structures, and human resources. The risks along the project route have been identified, prioritized, and mitigation strategies have been proposed to reduce these risks. The risks in the Tabriz Metro Line 2 project were categorized into six main groups: geotechnical hazards, excavation machinery, construction period, support and human resources, design and research phase, and management. Each category’s hazards were identified, evaluated, and key influencing factors were analyzed. Based on the risk analysis results, the risks were classified into high, medium, and low categories, and appropriate mitigation measures were suggested for each level of risk. Through the implementation of effective risk response techniques, high-risk hazards were reduced by 39%, and medium-risk hazards were reduced by 23%. This research provides valuable insights that can improve the overall quality and efficiency of the Tabriz Metro Line 2 tunneling project.